KEAMANAN, KEPERCAYAAN, HARGA, KUALITAS PELAYANAN SEBAGAI PEMICU MINAT BELI CUSTOMER ONLINE SHOP ELEVENIA - Bakhtiar, M. Rifki; Sunarka, Puji Setya (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The focus of this research is to analyze security, trust, price, service quality on customer's purchase intention on the online sales site at Elevenia.The samples in this study using purposive sampling method. Questionnaires 100 respondents who qualified as a sample. Data analysis tool used in the form of multiple linear regression with SPSS version 25. The results showed that: security (X1), Trust (X2), Price (X3), and service quality (X4) had a positive and significant effect on Purchase Intention. The study provides empirical evidence for marketplace to improve security, trust, price, service quality.